Kearifan lokal dalam praktik sosial-religius: Kajian tradisi Berateb Kampung masyarakat Kuala Alam - Prayugo, Prayugo; Muhajir, Muhajir; Amrizal, Amrizal (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study aims to uncover the values of local wisdom embedded in the Berateb Kampung tradition of the Kuala Alam village community in Bengkalis Regency. As a religious cultural heritage practiced since 1960, Berateb Kampung is performed annually as a communal prayer for protection, well-being, and the reinforcement of Islamic brotherhood (ukhuwah islamiyah). Using a qualitative approach and ethnographic method, data were collected through interviews, observations, and documentation. The findings reveal that Berateb Kampung is not merely a ritual but a symbolically rich practice that embodies social interaction, religious devotion, and spiritual reflection. Viewed through George Herbert Mead’s theory of symbolic interactionism, the tradition demonstrates how social meaning is shaped through collective symbolic action. From an Islamic legal perspective, the practice aligns with the concept of ‘urf (custom) and is acceptable as long as it does not contradict established religious texts (nash syar’i). Ultimately, Berateb Kampung represents a form of local wisdom that harmonizes religious and cultural values, preserves communal identity, and deserves safeguarding in the face of modern challenges.